2004
DOI: 10.1063/1.1829256
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic thermal quantities near the consolute point of the binary liquid mixture aniline–cyclohexane studied with a photopyroelectric technique and adiabatic scanning calorimetry

Abstract: We studied the thermal conductivity, thermal effusivity, and specific heat capacity at constant pressure of the critical binary liquid mixture aniline-cyclohexane near the consolute point, using a photopyroelectric (PPE) technique and adiabatic scanning calorimetry (ASC). According to recent theoretical predictions based on renormalization group theory calculations, a substantial (but not diverging) enhancement in the thermal conductivity in the homogeneous phase near the critical temperature was expected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…It was reported that the critical temperature was determined by fitting the experimental heat capacity data to Eqs. (27) and (28) simultaneously [26,28,29]. Unfortunately we failed to do so because of the strong correlation among the adjusting parameters.…”
Section: Isobaric Heat Capacity Per Unit Volumementioning
confidence: 98%
See 4 more Smart Citations
“…It was reported that the critical temperature was determined by fitting the experimental heat capacity data to Eqs. (27) and (28) simultaneously [26,28,29]. Unfortunately we failed to do so because of the strong correlation among the adjusting parameters.…”
Section: Isobaric Heat Capacity Per Unit Volumementioning
confidence: 98%
“…The temperature at the maximum point as postulated critical temperature was substituted into Eqs. (27) and (28), and then the experimental heat capacities within a range of ±3 K from the maximum point were fitted to Eqs. (27) and (28) with D + = D À = 0, and the standard deviation of the fit was calculated by:…”
Section: Isobaric Heat Capacity Per Unit Volumementioning
confidence: 99%
See 3 more Smart Citations